Prevalence of Abdominal Obesity and Metabolic Syndrome in Children and Adolescents: A Community Based Cross-Sectional Study - Nastaran AHMADI; Seyed Mahmood SADR; Mohammad Reza MOHAMMADI; Masoud MIRZAEI; Amir Hooshang MEHRPARVAR; Seyed Mojtaba YASSINI ARDEKANI; Mohammadtaghi SAREBANHASSANABADI; Neda NILFOROSHAN; Seyed-Ali MOSTAFAVI (Tehran University of Medical Sciences, 2020)
Background: Although the prevalence of abdominal obesity and metabolic syndrome has been widely studied in the adult population, little is known about it in children and adolescents especially in developing countries. This study aimed to determine the prevalence of abdominal obesity and metabolic syndrome among children and adolescents in Yazd Greater Area, Iran; over the period of 2016-2017. Methods: This study was part of a larger national study with a cross-sectional design. Using multistage cluster random sampling method, 1035 children, and adolescents of both sexes aged 6-18 yr were randomly selected from rural and urban districts in Yazd Greater Area, Iran. Components of metabolic syndrome, and anthropometry measured in the standard situation. Results: The prevalence of abdominal obesity in children 6-10 yr old was 13.2% in boys versus 24.7% in girls. The overall prevalence of metabolic syndrome according to International Diabetes Federation (IDF) criteria in adolescents aged 10-18 yr old was 7.6% (9.4% in boys). The most prevalent metabolic syndrome components were low HDL-cholesterol (56.2%) and abdominal obesity (27.8%). Conclusion: Comparatively, the prevalence of metabolic syndrome in Yazd is high. Low HDL-cholesterol levels and abdominal obesity were the most common component, and family history of heart disease, BMI, and male gender were the main determinants of metabolic syndrome in adolescents.